Opportunities and challenges for implementing cost accounting systems in the Kenyan health system - Elesban Kihuba; Adrian Gheorghe; Fiammetta Bozzani; Mike English; Ulla K. Griffiths (Global Health Action, 2016)
Background: Low- and middle-income countries need to sustain efficiency and equity in health financing on their way to universal health care coverage. However, systems meant to generate quality economic information are often deficient in such settings. We assessed the feasibility of streamlining cost accounting systems within the Kenyan health sector to illustrate the pragmatic challenges and opportunities. Design: We reviewed policy documents, and conducted field observations and semi-structured interviews with key informants in the health sector. We used an adapted Human, Organization and Technology fit (HOT-fit) framework to analyze the components and standards of a cost accounting system. Results: Among the opportunities for a viable cost accounting system, we identified a supportive broad policy environment, political will, presence of a national data reporting architecture, good implementation experience with electronic medical records systems, and the availability of patient clinical and resource use data. However, several practical issues need to be considered in the design of the system, including the lack of a framework to guide the costing process, the lack of long-term investment, the lack of appropriate incentives for ground-level staff, and a risk of overburdening the current health management information system. Conclusion: To facilitate the implementation of cost accounting into the health sector, the design of any proposed system needs to remain simple and attuned to the local context.